Revalidation and resurrection of Panaspis massaiensis (Angel, 1924) and the description of a new species of Panaspis Cope (Squamata: Scincidae) from south-eastern Kenya - Kilunda, Felista Kasyoka; Conradie, Werner; Wasonga, Domnick Victor; Jin, Jie-Qiong; Peng, Min-Sheng; Murphy, Robert W.; Malonza, Patrick Kinyatta; Che, Jing (Zootaxa, 2019)
Historically Panaspis wahlbergi (Smith, 1849) has been the only assignable species present in Kenya. Recent studies have shown that it comprises multiple cryptic species and the nominal species is now restricted to southern Africa. Newly collected mitochondrial data (16S rRNA) helped to resolve the status of the Kenyan populations, which revealed the presence of two distant related species. Pairwise distances show average 5.87% differences between the two Kenyan species, and 3.58–5.27% and 8.62–9.15% to nominal P. wahlbergi and P. maculicollis Jacobsen & Broadley, 2000 respectively. Ablepharus massaiensis Angel, 1924 was described from the Maasai plains near Nairobi, but has long been considered a junior synonym of P. wahlbergi. We herein resurrect Panaspis massaiensis comb. nov. as a valid species and describe a new species, Panaspis tsavoensis sp. nov. from the Tsavo Conservation Area in south-eastern Kenya. Morphological examinations of specimens reveal minor differences from each other as well as nominal forms of P. wahlbergi and P. maculicollis. Panaspis massaiensis comb. nov. shares with the P. wahlbergi group a white ventrolateral stripe but can be distinguished by the presence of 26 midbody scale rows versus 24. Panaspis tsavoensis sp. nov. on the other hand, lacks the white ventrolateral stripe, most similar to the P. maculicollis group but differs in that P. maculicollis breeding males have a black patch on the neck with diagonal rows of white spots. Panaspis massaiensis comb. nov. is widespread in the Kenyan and northern Tanzanian highlands, isolated dryland montane forests and rocky hills, while P. tsavoensis sp. nov. occur in the expansive arid lowlands of Tsavo Conservation Area and should be present in similar arid lowlands in northern Kenya as well as in adjacent Tanzania.